Hubungan Minat Baca Siswa Terhadap Kemampuan Mengapresiasikan Karya Sastra Siswa Kelas V Sdn Belotan 2 Kecamatan Bendo Kabupaten Magetan (Eduscotech, 2025)
Poetry is a form of literature, and it has been studied by children since elementary school. Everything related to poetry will be taught. The purpose of this study was to determine the relationship between students' reading interest and literary appreciation in Indonesian language lessons in fifth-grade students at Belotan 2 Public Elementary School, Bendo District, Magetan Regency. The study used a quantitative descriptive approach, involving 19 fifth-grade students at Belotan 2 Public Elementary School.The results showed that there was no relationship between students' reading interest and poetry appreciation, as the study obtained a score below the standard of -0.035, while the standard test score was